2018
DOI: 10.7717/peerj.5577
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNAs 34a, 146a, 320a and 542 in the synergistic anticancer effects of methyl 2-(5-fluoro-2-hydroxyphenyl)-1H- benzo[d]imidazole-5-carboxylate (MBIC) with doxorubicin in breast cancer cells

Abstract: Combination Index (CI) analysis suggested that MBIC and doxorubicin synergistically inhibited up to 97% of cell proliferation in ER+/PR+MCF-7 and triple negative MDA-MB-231 breast cancer cell lines. Moreover, treatment of the breast cancer cells with the combined drugs resulted in lower IC50 values in contrast to the individual drug treatment. Small noncoding microRNAs (miRNA) may function as non-mutational gene regulators at post-transcriptional level of protein synthesis. In the present study, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that, compared to individual miR-217 or miR-377 or transfections, the combination of miR-217 and miR-377 could not only reduce the expression of a HMOX1-3′UTR luciferase reporter but also reduce the protein expression and enzyme activity of heme oxygenase-1 (HMOX1, HO-1), indicating that the combination of miRNAs more effectively regulates HO-1 protein level in the presence of hemin than individual miRNAs . Furthermore, previous research demonstrated that miR-320a, miR-34a, and miR-542 have a synergistic function that is involved in the negative post-transcriptional regulation of survivin in MCF-7 cells . Previous studies have not reported the role of miR-4334, miR-219, and miR-338 in the NF-κB and p53 pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, compared to individual miR-217 or miR-377 or transfections, the combination of miR-217 and miR-377 could not only reduce the expression of a HMOX1-3′UTR luciferase reporter but also reduce the protein expression and enzyme activity of heme oxygenase-1 (HMOX1, HO-1), indicating that the combination of miRNAs more effectively regulates HO-1 protein level in the presence of hemin than individual miRNAs . Furthermore, previous research demonstrated that miR-320a, miR-34a, and miR-542 have a synergistic function that is involved in the negative post-transcriptional regulation of survivin in MCF-7 cells . Previous studies have not reported the role of miR-4334, miR-219, and miR-338 in the NF-κB and p53 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…46 Furthermore, previous research demonstrated that miR-320a, miR-34a, and miR-542 have a synergistic function that is involved in the negative post-transcriptional regulation of survivin in MCF-7 cells. 47 Previous studies have not reported the role of miR-4334, miR-219, and miR-338 in the NF-κB and p53 pathways. Furthermore, there is no report of the cooperative effects of these three miRNAs in TLRdependent inflammatory responses and in the apoptosis of intestinal epithelial cells.…”
Section: ■ Discussionmentioning
confidence: 99%